E-commerce Design Interaction with Voice User Interface using User-centered Design Approach - Rizky Faramita; Dessi Puji Lestari; Ginar Santika Niwanputri (IJNMT (International Journal of New Media Technology), 2019)
The rapid expansion of e-commerce has encouraged many platforms to serve their consumers better, including by providing state-of-the-art user interaction. Voice user interface is integrated in the e-commerce in order to allow users doing multitask while having handful activities and simplify features whose discoverability is low. The interface is designed using user-centered design approach, specifically ISO 9241-210:2010 methodology. In addition, the interface is verified by usability testing conducted in three iterations for two personas. Verification process of the design shows that high-fidelity prototype is 83.0% helpful and 70.0% effective.